Reduced Ca2+ transient amplitudes may signify increased or decreased depolarization depending on the neuromodulatory signaling pathway - Debnath, Arunima; Williams, Paul D. E.; Bamber, Bruce A. (Frontiers in Neuroscience, 2022)
Neuromodulators regulate neuronal excitability and bias neural circuit outputs. Optical recording of neuronal Ca2+ transients is a powerful approach to study the impact of neuromodulators on neural circuit dynamics. We are investigating the polymodal nociceptor ASH in Caenorhabditis elegans to better understand the relationship between neuronal excitability and optically recorded Ca2+ transients. ASHs depolarize in response to the aversive olfactory stimulus 1-octanol (1-oct) with a concomitant rise in somal Ca2+, stimulating an aversive locomotory response. Serotonin (5-HT) potentiates 1-oct avoidance through Gαq signaling, which inhibits L-type voltage-gated Ca2+ channels in ASH. Although Ca2+ signals in the ASH soma decrease, depolarization amplitudes increase because Ca2+ mediates inhibitory feedback control of membrane potential in this context. Here, we investigate octopamine (OA) signaling in ASH to assess whether this negative correlation between somal Ca2+ and depolarization amplitudes is a general phenomenon, or characteristic of certain neuromodulatory pathways. Like 5-HT, OA reduces somal Ca2+ transient amplitudes in ASH neurons. However, OA antagonizes 5-HT modulation of 1-oct avoidance behavior, suggesting that OA may signal through a different pathway. We further show that the pathway for OA diminution of ASH somal Ca2+ consists of the OCTR-1 receptor, the Go heterotrimeric G-protein, and the G-protein activated inwardly rectifying channels IRK-2 and IRK-3, and this pathway reduces depolarization amplitudes in parallel with somal Ca2+ transient amplitudes. Therefore, even within a single neuron, somal Ca2+ signal reduction may indicate either increased or decreased depolarization amplitude, depending on which neuromodulatory signaling pathways are activated, underscoring the need for careful interpretation of Ca2+ imaging data in neuromodulatory studies.